Tax Morale of Individual Taxpayers in the Micro, Small, and Medium Enterprises - Nisrina, Ulfah Laila; Lukman, Siti Diva Syarifah; Jusnia, Jusnia (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to review the tax morale of Individual Taxpayers who are MSMEs in Parepare City. Tax morale refers to the intrinsic motivation of individuals to fulfill their tax obligations voluntarily and without coercion. This research employs a descriptive qualitative approach, utilizing an in-depth interview method with four MSME actors who already possess a Taxpayer Identification Number. The analysis was conducted using the Theory of Planned Behavior (TPB) framework to understand how attitudes, subjective norms, and perceived behavioral control influence tax morale. The results showed that the tax morale of MSME players in Parepare City remains relatively low, despite most having a positive view of the importance of taxes. Low tax literacy, the perception that one is not obliged to pay because income is considered insufficient, and the lack of education and transparency in the tax system are the main obstacles to shaping tax morale.